Aktivitas Antibakteri Madu Lebah (Tetragonula laeviceps) terhadap Pertumbuhan Berbagai Macam Bakteri - Muhammad Hisyam Ihsan; Anggun Wicaksono; Ummi Hiras Habisukan; Yustina Hapida; Kurratul ‘Aini; Syarifah Syarifah; Rian Oktiansyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Tetragonula laeviceps belongs to a class of stingless bees that can produce honey. Tetragonula laeviceps honey contains compounds that are antibacterial. The purpose of this study was to determine the effect of stingless bee honey on the growth of the bacteria Salmonella typhi that causes typhus, Escherichia coli causes diarrhea, and Staphylococcus aureus causes skin infections, and can contribute to Eubacteria material in class X SMA. This research was conducted at the Biology Education Laboratory, State Islamic University Raden Fatah Palembang. The method used was a completely randomized design (CRD), an experimental study with 5 repetitions divided into 4 treatments (3%, 5%, 7%, and 9%), and 1% tetracycline as positive control with distilled water as diluent. The results of this study were that the 9% concentration treatment showed the greatest effect. The size of the inhibition zone of 9% honey Tetragonula laeviceps for Salmonella typhi was 1.23 mm, Escherichia coli was 3.68 mm, and Staphylococcus aureus was 3.09 mm. The resulting inhibition zone has a weak category because it is < 5 mm. Based on the analysis of the calculations carried out by the One Way ANOVA test for each bacteria, which has a value of 0.00 <0.05, which means that each treatment has a significant effect, then proceed with the Duncan Significant Distance Difference (BJND) test, where the DMRT results for honey bee treatment stingless was smaller than the mean diameter of the positive control, which meant that each treatment of stingless bee honey was very significantly different from the positive control. This shows that Tetragonula laeviceps honey has the effectiveness of inhibiting the growth of Salmonella typhi, Escherichia coli, and Staphylococcus aureus.